ANALYSIS OF STUDENTS' MATHEMATICAL COMMUNICATION SKILLS ON STATISTICAL MATERIAL: ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS SISWA PADA MATERI STATISTIK - Tiara Tanjung, Yulia (UPMI Proceeding Series, 2023)
Mathematical communication skills have an important role to help students develop and explore imagination, take an active role in learning activities, and express thoughts in solving a mathematical problem. This research is a qualitative descriptive research, which aims to reveal students' mathematical communication skills in solving problems on Statistics material. The subjects of the study were students of grade VIII consisting of 25 students. The number of subjects in this study consisted of 10 students who were categorized into four levels based on the division of communication skill levels. This research data was obtained from mathematical communication skills tests and interviews. The results showed that students who had very high communication were able to meet all indicators of mathematical communication, students who had high communication were able to meet four indicators of mathematical communication, students who had low communication were able to meet two indicators of mathematical communication, while students who had very low communication were unable to meet five indicators of mathematical communication.